A case study of a novice teacher’s implementation of assessment for learning tools in a year one English classroom / Sharon Linang Jimbun - Jimbun, Sharon Linang (2015)
In 2011, School Based Assessment (SBA) has officially made its way into the Malaysian education system starting from Year 1. The advent of SB A gives rise to the usage of assessment for learning tools and practices in the classroom. The purpose of this study is to investigate the assessment for learning tools and strategies used by a novice teacher in a Year 1 English classroom. The assessment for learning tools are the selection of task type, usage of feedback and questioning while the strategies are the inclusion of assessment for learning practices that the novice teacher puts into her teachings. This case study employed interviews, class observation and document analysis as part of the data collection. In addition, the data were transcribed and analysed using thematic analysis. The findings indicated that the novice teacher preferred pair or group work type of task and employs positive feedback and high usage of low order thinking skills type of questioning. From this case study, it is highly recommended that teachers need to be trained well in the actual usage of assessment for learning tools and strategies to make it a realized practice in the day-to-day lesson. Future research should look into the revision of the content and learning documents pertaining to SBA in general and assessment for learning in particular. Selection of the prescribed teaching and learning resources should also be revised to optimize the usage of assessment for learning in the classroom.